Input Substitution analysis of Paddy Rice Farming in Different Land Area Strata in Bengkulu Province - Teresha Amanda; Ketut Sukiyono; Bambang Sumantri (Demeter: Journal of Farming and Agriculture, 2025)
The objectives of this study are 1) Analyze what production factors affect rice production in different strata of land area in Bengkulu Province. 2) Analyze the level of input substitution in paddy rice farming at different strata of land area in Bengkulu Province. The location determination method uses Three stages cluster sampling and the Proportionate Stratified Random Sampling sampling method, the sample number of 175 rice farmers. The data analysis method used is the cobb-douglass and MRTS production functions. 1) The results of the analysis show that only the land area factor (ha) has a real effect on production in all strata of land area. Meanwhile, in strata III and the combination of factors the use of female labor has a real effect on production, and on the combined land area the use of KCL fertilizer has a real effect on production. 2) Only the combination of male labor to female labor in Strata I is fully substituted with a substitution elasticity (ES) value greater than 1 (≥ 1) while in combination the use of fertilizer inputs is only partially substituted. Meanwhile, in strata II, III, and combined, both the combination of fertilizer inputs and male and female labor are only partially substituted.